2015
DOI: 10.1002/ajh.24094
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphoma: 2015 update on diagnosis, risk‐stratification, and clinical management

Abstract: Disease Overview: Mantle cell lymphoma (MCL) is a non‐Hodgkin lymphoma characterized by involvement of the lymph nodes, spleen, blood and bone marrow with a short remission duration to standard therapies and a median overall survival (OS) of 4‐5 years.Diagnosis: Diagnosis is based on lymph node, bone marrow, or tissue morphology of centrocytic lymphocytes, small cell type, or blastoid variant cells. A chromosomal translocation t (11:14) is the molecular hallmark of MCL, resulting in the overexpression of cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 62 publications
0
60
0
1
Order By: Relevance
“…Modern chemoimmunotherapies alone, or as induction followed by auto-HCT in first remission, undoubtedly have improved patient outcomes; however, disease relapse eventually occurs for nearly all patients. [49]…”
Section: Mantle Cell Lymphoma (Mcl)mentioning
confidence: 99%
“…Modern chemoimmunotherapies alone, or as induction followed by auto-HCT in first remission, undoubtedly have improved patient outcomes; however, disease relapse eventually occurs for nearly all patients. [49]…”
Section: Mantle Cell Lymphoma (Mcl)mentioning
confidence: 99%
“…In this setting, both techniques seem to have distinct diagnostic accuracy in aggressive lymphomas, showing reduced sensitivity for the detection of low-volume bone marrow involvement in i-NHLs, where imaging modalities are complementary to bone marrow biopsy [32,33]. In fact, bone marrow biopsy is still recommended in NHL [15], being essential for both diagnosis and evaluation of marrow cellularity and hematopoietic reserve [34][35][36], while it is no longer required for Hodgkin's lymphoma [15]. Finally, previous studies have shown the potential role of WB-MRI in the early detection of osteonecrotic lesions in lymphoma patients treated with high doses of corticosteroids, allowing prompt referral of these patients to orthopaedists and providing the opportunity for early intervention [37][38][39].…”
Section: Imaging Monitoring and Wwmentioning
confidence: 99%
“…However, about 2% of these tumors are cyclin D1 negative. [5] In addition, cyclin D1 has also been found to be positive in other histological types of hematopoietic and lymphoid tumors. For example, cyclin D1 was found to be overexpressed in about half the plasma cell myelomas.…”
Section: Discussionmentioning
confidence: 99%